The Effect of Used Oil Mixing Variations And Curing Time To The Stability of Recycled Asphalt Mixture - Bowoputro, Hendi; Djakfar, Ludfi; Muslim, Muhamad Iqbal; Rizaldi, Taqwa (Rekayasa Sipil, 2013)
The aim of this research is to determine the relationship pattern between the variation in levels of used oil and curing time to Marshall Stability of recycled asphalt mixture, and to determine levels of used oil and curing time were used to obtain the optimum stability of recycled asphalt mixture. Asphalt recycled used in this research is from asphalt pavement milling in front of the Head Office of Brawijaya University. Marshall test is used to test recycled asphalt mixture with a content rate of 4%,5%,6%,7% ,8% used oil and curing time 4 until 7 days. Test result indicated that the value of stability decreased with increasing levels of addition of used oil, but at 8% content of used oil, stability increased although itâs not significant. Stability value increases with increasing levels of curing time, but at the 5 th day of curing time, the stability is decreased although itâs not significant. The optimum levels of used oil is 4.0%. Optimum curing time is 7 days.Â